Understanding Cultural Identification Through Intersubjective Cultural Representation. (November 2015) - Wan, Ching
Intersubjective cultural representation refers to a collective's common representation of a culture. Such representation provides a meaningful basis for individuals to develop identification with the culture. Specifically, the more an individual's personal values are aligned with values intersubjectively represented to be important to a culture, the more strongly the individual would identify with the culture. Consideration of the role of intersubjective representation in cultural identification has implications for future research on the development of cultural identity, especially in multicultural contexts.